2020
DOI: 10.1186/s12943-020-01250-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive elaboration of the cGAS-STING signaling axis in cancer development and immunotherapy

Abstract: Cellular recognition of microbial DNA is an evolutionarily conserved mechanism by which the innate immune system detects pathogens. Cyclic GMP-AMP synthase (cGAS) and its downstream effector, stimulator of interferon genes (STING), are involved in mediating fundamental innate antimicrobial immunity by promoting the release of type I interferons (IFNs) and other inflammatory cytokines. Accumulating evidence suggests that the activation of the cGAS-STING axis is critical for antitumor immunity. The downstream cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 175 publications
(263 reference statements)
2
103
0
Order By: Relevance
“…We observed that STING pathway activation in leukemia cells resulted in the generation of ROS, which could be a main executor of the cytotoxicity induced by autophagosome inhibitors. STING pathway activation can stimulate IκB kinase and TANK-binding kinase 1 to activate two distinct transcription factors, NF-κB and IRF3, respectively, and both these factors can induce the expression of several antimicrobial and inflammation-related molecules, including ROS 20 22 . We observed that an autophagosome inhibitor enhanced the gene expression of TNF-α , IL-12 , and MCP-1 , in a STING pathway-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that STING pathway activation in leukemia cells resulted in the generation of ROS, which could be a main executor of the cytotoxicity induced by autophagosome inhibitors. STING pathway activation can stimulate IκB kinase and TANK-binding kinase 1 to activate two distinct transcription factors, NF-κB and IRF3, respectively, and both these factors can induce the expression of several antimicrobial and inflammation-related molecules, including ROS 20 22 . We observed that an autophagosome inhibitor enhanced the gene expression of TNF-α , IL-12 , and MCP-1 , in a STING pathway-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…TREX1 and the cGAS-STING pathway have been implicated in the tumor microenvironment [reviewed in refs ( 39 45 )]. TREX1 activity has been negatively correlated with outcomes in multiple cancers ( 46 48 ).…”
Section: A Brief History Of Trex1mentioning
confidence: 99%
“…In addition to cGAMP-generated cyclic di-nucleotides, the STING signaling axis is also activated by other stimuli such as cyclic di-nucleotides produced by bacteria, mitochondrial DNA, cytosolic chromatin, and micronuclei [ 154 ]. Activated STING translocates from the ER to the Golgi, where it recruits TBK1 and multimerizes, forming the STING-signalosome [ 155 , 156 ].…”
Section: Negative Regulation Of Cytosolic Dna Sensor Pathwaysmentioning
confidence: 99%